Les espaces verts de la ville d’Assise - Giulia Giacchè (Projets de Paysage)
This paper focuses on the management of green open spaces of Assisi town. Since 2000 the influx of more than one million tourists each year and the inscription at “World Heritage List” have played a role in the way of considering and managing open spaces. The green open spaces inside or outside Assisi town are a part of a global planning project, enhancing cultural, heritage and landscape value. Three examples are used to figure out : the first, which involves the planning of natural and open spaces around the town, the second, which interest a project of green space inside the city and the third, which considered the management of olive tree in the Regional Park of Subasio Mountains. The richness of this case study is that it combines two viewpoints on the landscape. On the one hand the development of standards and best practices to follow (such as "Guidelines of the landscape") to promote landscape conservation, on the other hand the revert to the ancient landscape considered common heritage to project new spaces.